An open window: the crucial role of the gut-brain axis in neurodevelopmental outcomes post-neurocritical illness - Victoria Ronan (Frontiers in Pediatrics)
Among patients admitted to the pediatric intensive care unit, approximately 10% are discharged with a new functional morbidity. For those who were admitted with a neurocritical illness, the number can be as high as 60%. The most common diagnoses for a neurocritical illness admission include traumatic brain injury, status epilepticus, post-cardiac arrest, hypoxic ischemic encephalopathy, meningo/encephalitis, and stroke. The gut-brain axis is crucial to childhood development, particularly neurodevelopment. Alterations on either side of the bidirectional communication of the gut-brain axis have been shown to alter typical development and have been associated with autism spectrum disorder, anxiety, sleep disturbances, and learning disabilities, among others. For those patients who have experienced a direct neurologic insult, subsequent interventions may contribute to dysbiosis, which could compound injury to the brain. Increasing data suggests the existence of a critical window for both gut microbiome plasticity and neurodevelopment in which interventions could help or could harm and warrant further investigation.